2014
DOI: 10.2139/ssrn.2677678
|View full text |Cite
|
Sign up to set email alerts
|

Japan's Agri-Food Sector and the Trans-Pacific Partnership

Abstract: Japan's agriculture has been inward oriented, protected by trade barriers from foreign competition. Even though the share of Japan's food consumption provided by Japanese production has gradually fallen, Japan's farm sector remains the second-largest among the countries negotiating the Trans-Pacific Partnership (TPP). Japan's food industry is increasingly integrated with TPP economies, although the TPP share of Japan's agricultural imports has fallen over time. The proposed TPP agreement would lead to more agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…TPP would have impact on Japan's agricultural import. It is suggested that TPP agreement would lead to more imports from other TPP participation countries, "dominating the total agricultural trade impact of such an agreement" [6], despite it would have little reduction on domestic production. Imports from TPP partners are substantial and most of them are relatively steady, though actual values have dropped due to the increasing imports from China and Thailand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…TPP would have impact on Japan's agricultural import. It is suggested that TPP agreement would lead to more imports from other TPP participation countries, "dominating the total agricultural trade impact of such an agreement" [6], despite it would have little reduction on domestic production. Imports from TPP partners are substantial and most of them are relatively steady, though actual values have dropped due to the increasing imports from China and Thailand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, Japan's food industry, with less protection and high input costs, became outward-oriented, with global investments in farming, food manufacturing and distribution and retailing (Dyck and Arita 2014). The Japanese soybean processing industry, for example, has been an active investor in overseas farms, processing facilities and trading companies.…”
Section: Trade Policy and Japanese Food And Agriculturementioning
confidence: 99%
“…Further, in 2012, Japanese households spent over one fifth of consumption on food-related items compared to only 11 per cent for American consumers (United States Department of Agriculture 2013). In 2013, the value of agricultural exports was less than 4 per cent of domestic agricultural sales, and agricultural imports had grown more slowly than overall imports for more than two decades (Dyck and Arita 2014).…”
Section: Trade Policy and Japanese Food And Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…For Japan, tariffs for cassava starch are relatively high, and further liberalization could lead to significant gains. In the case of rice, Japan has a strong preference for shortgrain japonica rice and, even at zero tariffs, the country is unlikely to import much more of the long-grain indica rice that is grown in Vietnam (Dyck and Arita, 2014). Nevertheless, while Japan's consumption of indica rice is limited and unlikely to grow, indica is still a sizable import market (200,000-300,000 tons annually in recent years), and Vietnamese rice could potentially replace the indica rice imports which are currently dominated by Thai rice.…”
Section: Export Tariff Structurementioning
confidence: 99%